On some boundary-value problems with a shift on characteristics for a mixed equation of hyperbolic-parabolic type - Eleev, V. A.; Kumykova, S. K. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove theorems on the existence and uniqueness of solutions of nonlocal boundary-value problems with shift for mixed second- and third-order equations of hyperbolic-parabolic type.